Synthesis and characterization of CuO/ZnO/CNTs thin films on copper substrate and its photocatalytic applications - D. Saravanakkumar; Hicham Abou Oualid; Younes Brahmi; A. Ayeshamariam; M. Karunanaithy; A. Mohamed Saleem; K. Kaviyarasu; S. Sivaranjani; M. Jayachandran (Elsevier, 2019)
In this work, Jet nebulizer technique was used to prepare thin films of CuO (1%) doped with ZnO-carbon nanotubes (CuO/ZnO/CNTs). The morphology, surface roughness, surface pattern, and elemental composition of the thin films were examined by X-ray diffraction, scanning electron microscopy, atomic force microscopy, Raman analysis, PL emission and transmission electron microscopy, respectively. The photocatalytic activity of pure CuO/ZnO/CNTs was examined using the rate of degradation of Rhodamine-B (RhB) under the effect of UV-B irradiation. UV-Vis analysis revealed that the average crystal sizes were uniform with values of 24.89, 24.412, and 23.711 nm. The maximum absorptive energy of RhB was found to be at 551 nm. Keywords: Jet nebulizer, CuO/ZnO/CNTs, Morphology, Surface roughness, Surface pattern photocatalytic, Uv-b irradiation, Rhb degradation and crystal size